Establishment of the World Health Organization First International Standard for Factor XII, Plasma, Human - Wilmot, Helen V.; Hockley, Jason; Rigsby, Peter; Gray, Elaine (Frontiers in Medicine, 2018)
Until recently, the role of factor XII (FXII) in haemostasis was not considered to be important since patients with FXII deficiency do not present with bleeding. The activation of FXII by agents including mast cells and platelet polyphosphates suggests it may have a role in thrombogenesis. Inhibition of FXII therefore presents an option for antithrombotic therapy and antibodies and inhibitors are already in development. Assays for FXII will be required to support these technologies and an international standard (IS) for FXII would be useful for the development of these methods and for clinical monitoring of patients. The purpose of this study was to develop an International Standard for FXII, with values for functional activity (FXII:C) and antigen (FXII:Ag). Double-spun normal plasma was pooled, filled into siliconized glass ampoules, and freeze-dried to prepare the candidate material. Data from 20 laboratories using the one-stage clotting assay was used to assign the functional activity value in units (u). The antigen value was calculated using data from 8 laboratories that carried out antigen assays. Each laboratory was requested to collect two local normal plasma pools. Units of activity and antigen were calculated relative to these pools, as is usual for new coagulation factor analytes. The amount of activity or antigen in 1 ml of normal plasma from each pool was taken to be 1 unit. A total of 566 donors were used across the pools for the FXII:C study, and 216 donors for the FXII:Ag study. The overall geometric mean per ampoule for FXII:C was 0.86 u and for FXII:Ag was 0.80 u. The inter-laboratory variation was 10 and 11%, respectively (expressed as geometric coefficient of variation). Based on these data, the candidate was deemed suitable for use as an IS for FXII. In 2017, the candidate was established by the World Health Organization (WHO) Expert Committee on Biological Standardization as the WHO 1st IS for blood coagulation factor XII, plasma (National Institute for Biological Standards and Control code 15/180). The values assigned were 0.86 international units (IU) of functional activity (FXII:C) per ampoule and 0.80 IU/ampoule of antigen (FXII:Ag).